2016
DOI: 10.1136/jech-2016-208185
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic differences in health check-ups and medically certified sickness absence: a 10-year follow-up among middle-aged municipal employees in Finland

Abstract: Age-based health check-ups reduced subsequent sickness absence and should be promoted. Attendance to health check-ups should be as high as possible. Contextual factors need to be taken into account when applying the results in interventions in other settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 20 publications
0
12
0
Order By: Relevance
“…However, some studies have found HCU to be a valuable component of Finnish OHC. The targeted HCU may work as triggers for interventions to address poor work ability (9,40) while they can also work as interventions themselves (8). The health education given during HCU may have some effect in the prevention of occupational asthma and accidents (41).…”
Section: Discussionmentioning
confidence: 99%
“…However, some studies have found HCU to be a valuable component of Finnish OHC. The targeted HCU may work as triggers for interventions to address poor work ability (9,40) while they can also work as interventions themselves (8). The health education given during HCU may have some effect in the prevention of occupational asthma and accidents (41).…”
Section: Discussionmentioning
confidence: 99%
“…However, earlier prevention where the intervention is implemented before diagnosis could be more efficient [70]. For example, in a Finnish study, age-based health check-ups offered by the occupational health care reduced subsequent SA and those in the lower occupational classes participated actively, but socioeconomic differences were not reduced [71]. If the intervention is not targeted to all employees, previous evidence shows that objective selection of the participants who could benefit for early intervention is more effective and should be promoted in future interventions [72].…”
Section: Discussionmentioning
confidence: 99%
“…Piha et al . () reported that the income level of employees is an influential factor in attending health checks. Lee et al .…”
Section: Datamentioning
confidence: 94%
“…Piha et al . () found that employees with lower socio‐economic positions participate more actively in health checks than do other cohorts. Screening history and general practice visits are also influential in the attendance rate of health checks (Labeit et al ., ).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation